Temperature Control and Monitoring of Mass Concrete in Flood Control Wall Floor - PENG Qian; YAO Shunyu; LIU Zhanling; YANG Wanlun (Renmin Zhujiang)
In the process of mass concrete construction,the crack temperature control directly affects the quality of construction.Taking the mass concrete construction of a flood control wall floor in Huangpu River as an example,in order to avoid the occurrence of harmful cracks,this paper takes the corresponding temperature control measures,and conducts the temperature monitoring.The measured data of typical measuring points show that the inner surface,surface and environmental temperature differences of each measuring point are within the limits,and no temperature cracks are found on the concrete surface after removal of form,which verifies the rationality of the design and temperature control construction measures,and provides guidance for the implementation of subsequent projects.